Three-Weekly Doses of Azithromycin for Indigenous Infants Hospitalized with Bronchiolitis: A Multicentre, Randomized, Placebo-Controlled Trial - McCallum, Gabrielle B.; Morris, Peter S.; Grimwood, Keith; Maclennan, Carolyn; White, Andrew V.; Chatfield, Mark D.; Sloots, Theo P.; Mackay, Ian M.; Smith-Vaughan, Heidi; McKay, Clare C.; Versteegh, Lesley A.; Jacobsen, Nerida; et al. (Frontiers in Pediatrics, 2015)
Background Bronchiolitis is a major health burden in infants globally, particularly among Indigenous populations. It is unknown if 3 weeks of azithromycin improve clinical outcomes beyond the hospitalization period. In an international, double-blind randomized controlled trial, we determined if 3 weeks of azithromycin improved clinical outcomes in Indigenous infants hospitalized with bronchiolitis. Methods Infants aged ≤24 months were enrolled from three centers and randomized to receive three once-weekly doses of either azithromycin (30 mg/kg) or placebo. Nasopharyngeal swabs were collected at baseline and 48 h later. Primary endpoints were hospital length of stay (LOS) and duration of oxygen supplementation monitored every 12 h until judged ready for discharge. Secondary outcomes were: day-21 symptom/signs, respiratory rehospitalizations within 6 months post-discharge and impact upon nasopharyngeal bacteria and virus shedding at 48 h. Results Two hundred nineteen infants were randomized (n = 106 azithromycin, n = 113 placebo). No significant between-group differences were found for LOS (median 54 h for each group, difference = 0 h, 95% CI: −6, 8; p = 0.8), time receiving oxygen (azithromycin = 40 h, placebo = 35 h, group difference = 5 h, 95% CI: −8, 11; p = 0.7), day-21 symptom/signs, or rehospitalization within 6 months (azithromycin n = 31, placebo n = 25 infants, p = 0.2). Azithromycin reduced nasopharyngeal bacterial carriage (between-group difference 0.4 bacteria/child, 95% CI: 0.2, 0.6; p < 0.001), but had no significant effect upon virus detection rates. Conclusion Despite reducing nasopharyngeal bacterial carriage, three large once-weekly doses of azithromycin did not confer any benefit over placebo during the bronchiolitis illness or 6 months post hospitalization. Azithromycin should not be used routinely to treat infants hospitalized with bronchiolitis. Clinical trial registration The trial was registered with the Australian and New Zealand Clinical Trials Register: Clinical trials number: ACTRN1261000036099.